HUBUNGAN ANTARA ADEKUASI HEMODIALISIS DENGAN KUALITAS TIDUR PADA PASIEN GAGAL GINJAL KRONIK YANG MENJALANI HEMODIALISIS DI RUMAH SAKIT PKU MUHAMMADIYAH YOGYAKARTA - Rocharini Dwi Putri (FKU 16 UMY 015, 2016)
Background: Chronic Kidney Disease (CKD) is a clinical condition which is indicated by lower glomerulate filtrate rate and higher albuminuria. End-Stage Renal Disease (ESRD) is the last stadium of CKD which need renal replacement therapy, such as hemodialysis. Adequacy of hemodialysis should be measured to determine the success of hemodialysis. Sleep disorders are prevalent complication in hemodialysis patients. Inadequate hemodialysis is one of the factors that affecting sleep quality of patients on hemodialysis. Objective: To find out the relationship between adequacy hemodialysis with the sleep quality of end-stage renal disease’s patients on maintenance hemodialysis in PKU Muhammadiyah Yogyakarta Hospital. Methods: This study was an analytical cross-sectional which results arepresented in descriptive followed by bivariate analysis using Chi-Square Test and Fisher’s Exact Test to determine the correlation between two variables. The subjects were ESRD patients on maintenance hemodialysis of PKU Muhammadiyah Yogyakarta Hospital which meet the inclusion criteria. The research instruments werea questionnaire of PSQI and medical record. Result and Discussion: Statistically, there is no relations between hemodialysis adequacy and the sleep quality of ESRD patients in PKU Muhammadiyah Yogyakarta Hospital (p = 0,446). Conclusion: There is no relations between adequacy hemodialysis with the sleep quality of end-stage renal disease’s patients on maintenance hemodialysis in PKU Muhammadiyah Yogyakarta Hospital.